ANALISIS FAKTOR RISIKO KELUHAN DERMATITIS KONTAK PADA PETANI DI DESA TEGAL GONDO TAHUN 2023 - Nindi Isnaini (2023)
Farmers' indiscipline in using PPE when using chemicals is one of the risk factors for contact dermatitis. This study aims to determine the risk factors associated with complaints of contact dermatitis in farmers in Tegal Gondo village. The research design used was cross-sectional with purposive sampling technique and a sample of 115 respondents. The instrument used was a modified questionnaire from previous research and had been tested for validity and reliability. Data analysis used univariate analysis and bivariate analysis with chi-square test. The results of the analysis test showed that 50.4% of farmers experienced contact dermatitis with a variable history of atopy (P-value 0.000) and personal hygiene (P-value 0.040) having a relationship with complaints of contact dermatitis. The variables of age (P-value 0.564), length of contact (P-value 0.648), frequency of exposure (P-value 0.937), type of chemical (P-value 0.161), knowledge (P-value 0.215), and use of PPE (P-value 0.060) are not associated with complaints of contact dermatitis. Based on these results, the factors of atopy history and personal hygiene are risk factors for contact dermatitis complaints for farmers. It is recommended that the Tegal Gondo village government provide facilities for washing hands with clean water at several points of the rice fields and farmers who experience complaints of contact dermatitis to examine themselves to the nearest health care facility.